Mechanical activation-assisted combustion synthesis of in situ aluminum matrix hybrid (TiC/Al2O3) nanocomposite. Issue 15 (15th November 2016) - Mehrizi, M. Zarezadeh; Beygi, R.; Mostaan, H.; Raoufi, M.; Barati, A.
Abstract: The aim of this study is the synthesis of aluminum-based metal matrix nanocomposites reinforced with in situ TiC and Al2 O3 hybrid reinforcements by the mechanically activated combustion synthesis. The composites were fabricated from the powder blends consisting of aluminum, rutile and graphite with an excess amount of aluminum following the 14Al–3TiO2 −3C system and milled up to 30 h. Phase evolutions and structural changes during ball milling and combustion synthesis were studied by X-ray diffraction technique, field-emission gun scanning electron microscopy and transmission electron microscopy. The results showed that even after 10 h of milling, no new phases were formed. The increasing of milling time caused the broadening of all the peaks indicating a decrease in the crystallite size and an increase in the lattice strain. These results showed that Al, C and TiO2 nanocrystallites could be obtained during the ball-milling process. The result of combustion synthesis of un-milled powders confirmed that no new phases were found. In comparison with un-milled powder mixture, the 10 h milled powder could be easily ignited and XRD, HRSEM and TEM results confirmed that Al/TiC–Al2 O3 nanocomposite was successfully synthesized through combustion method from the mechanical activated powder mixture. Mechanical activation via high energy ball-milling provided to the initial powder mixture extra energy, which is needed to increase the reactivity of powder mixture and to make possible the ignition and the sustaining of combustion.